A new species and two new combinations in the genus Strotihypera Kononenko & Han, 2011 (Lepidoptera, Noctuidae, Noctuinae: Elaphriini). A postscript to the description of the genus Strotihypera - Han, H. L.; Kononenko, V. S. (Zootaxa, 2015)
Elaphriini is a small tribe of the subfamily Noctuinae with predominantly New World distribution. Only three genera, Elaphria Hübner, 1818 with four species, Galgula Guenée, 1852 with one species (Fibiger & Hacker 2010) and Strotihypera Kononenko & Han, 2011 with one species are known from the Eurasia. The majority of species occurs in tropical and subtropical regions. The review of Eurasian Elaphriini with description of the new genus Strotihypera has recently been published by Kononenko & Han (2011). In the subsequent years in the result of intensive collecting in South West China we found a new species allied to Strotihypera flavipuncta (Leech, 1889) and two related species Strotihypera ochreipuncta (Wileman, 1914), comb. n. and “Hyperstrotia” macroplaga (Hampson, 1907), comb. n. The description of a new species and the review of two of its allies are presented here as a postscript to the description of the genus Strotihypera (Kononenko & Han 2011).